Impregnated fly ash sorbent for cesium-137 removal from water samples - Silliková, Veronika; Dulanská, Silvia; Horník, Miroslav; Jakubčinová, Jana; Mátel, Ľubomír (Journal of radioanalytical and nuclear chemistry, 2020)
Cesium-137 is an important indicator of radioactive pollution in the aquatic environment. The aim of this study was to increase the sorption capacity of fly ash by its modification using hexacyanoferrate impregnation. According to the results, the Langmuir model was more likely to be correct than the Freundlich model. The maximum sorption capacity q max was 1.59 mmol/g, i.e. 210 mg Cs + per 1 g of the prepared sorbent. There was no significant decrease in the sorption capacity in the presence of both monovalent and divalent competitive cations. At the volume of 1–42 L the yield of Cs sorption was above 90%.